PENGUJIAN EFISIENSI SETENGAH KUAT SECARA INFORMASI TERHADAP PENGUMUMAN INISIASI DEVIDEN - Musaroh Musaroh (LPPM UNY, 2005)
Abstract This research explores the efficiency of semi-strong-informed capital market in Jakarta Stock Market toward the announcement of the dividend initiation. The testing focused on the effort to show the influence from the announcement of the dividend initiation toward the abnormal return of the capital at the event date of the announcement. It also tries to show the speed of adjustment from the stock price to equilibrium price. The result of the research shows that Indonesian Stock Market, represented by Jakarta Stock Market, has been semi-strong-informed efficient toward the announcement of the dividend initiation. It is proven by the positive and significant (6% at date of announcement) content of information in the announcement of the dividend, and the 1 day speed of the adjustment from market reaction toward the announcement of the dividend initiation. This research also support the agency cost and the asymentry information. Keywords: dividend initiation, semi-strong-informed capital market, abnormal return, Initial Public Offering